As subjetividades contemporâneas sob o signo do consumo – os ideais narcísicos na publicidade da TV: produção e consumo - Severiano, Maria de Fátima Vieira (1999)
It is characteristic of our time, the exaltation of a narcissistic “individualism”, expressed through a celebration of consume emblems as a way of acquiring a “plural” individuality. We investigate some elements constitutive of the contemporary subjectivity related to this phenomenon, analysing theoretical and empirically the values professed on the commercial TV publicity, and its forms of production and consume. We build our research on the top of both the critic of Adorno to the cultural industry and the analysis of the narcissism phenomenon on the psychological (Freud) and cultural (Lasch) perspective. We interviewed professional of marketing and college students in Brasil and Spain. They were selected according with a scale for measuring narcissistic features that we elaborate. It could be observed distinct kinds and degrees of identification of the students with the values emphasised by the commercial advertisements. This tact corroborated our hypotesis, according with, individuals with greater narcissistic inclination are more susceptible to propaganda mechanisms. Furthermore, the exaltation of the narcissistic features rather than favouring the individuation process, preserves the “unidimensional” character of advanced industrial societies.